The instability of preferences: Uncertain futures and the incommensurable and intersubjective nature of value(s) - Richard Bronk; Jens Beckert (Max Planck Institute for the Study of Societies, 2022)
The default assumption of standard economics is to treat preferences as exogenously 'given', consistent with one another, 'revealed' by past choices, and context independent. There has been increased interest recently (within behavioural economics) in the impact of inconsistent or irrational preferences and (more broadly) in dynamic and endogenous preferences. This paper builds on these challenges to standard assumptions by analysing the pivotal role of three aspects of preference formation in explaining capitalist dynamics and market instability. These are the constant creation of new preferences and the indeterminacy of choice sets in the context of widespread product innovation; the moral indeterminacy implied by conflicting and incommensurable social norms attaching to market goods where there is no single scale of value and hence no unique set of rational trade-offs; and, lastly, the contingent social and market construction of the product differentiation, quality attribution, and value assessments central to preference formation. The paper concludes by considering implications for economics as a discipline. – – Eine Standardannahme in den Wirtschaftswissenschaften ist, dass Präferenzen exogen 'gegeben', konsistent, durch vorausgegangene Entscheidungen offenbart und kontextunabhängig sind. In Kreisen der Verhaltensökonomie ist neuerlich ein gestiegenes Interesse an den Auswirkungen widersprüchlicher oder irrationaler Präferenzen und - etwas weiter gefasst - an dynamischen und endogenen Präferenzen zu verzeichnen. Das vorliegende Papier geht von diesen Kritiken aus und untersucht die zentrale Rolle dreier Aspekte der Präferenzbildung zur Erklärung von kapitalistischer Dynamik und Marktinstabilität: 1) die konstante Schaffung neuer Präferenzen und die Unbestimmtheit von Auswahlkriterien angesichts einer großen Anzahl von Produktinnovationen; 2) die moralische Unbestimmtheit aufgrund sich entgegenstehender und nicht vergleichbarer sozialer Normen, die mit Marktgütern in Zusammenhang gebracht werden, ohne das Vorhandensein einer allgemeingültigen Werteskala und somit ohne eine feste Auswahl an möglichen rationalen Ausgleichen; und 3) die ungewisse soziale und marktbezogene Zusammensetzung von Produktdifferenzierung, Qualitätszuschreibung und Wertbeimessung, die für die Präferenzbildung von zentraler Bedeutung sind. Das Papier schließt mit Überlegungen, welche Implikationen sich daraus für die Disziplin der Wirtschaftswissenschaften ergeben könnten.
hdl:21.11116/0000-000A-2440-5
Keywords: 300; endogenous preferences; incommensurable values; preference cascades; preference formation; product differentiation; quality uncertainty; endogene Präferenzen; inkommensurable Werte; Präferenzbildung; Präferenzkaskaden; Produktdifferenzierung; Qualitätsunsicherheit